Fiscal multipliers in South Africa: The importance of financial sector dynamics - Konstantin Makrelov; Channing Arndt; Robert H. Davies; Laurence Harris (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We analyse implications of financial sector dynamics for fiscal expenditure multipliers in recessionary conditions. We employ a stock-and-flow-consistent model for South Africa with four financial instruments and detailed balance sheets for the household, government, financial, non-financial, and foreign sectors, and the Reserve Bank. The increase in government expenditure positively affects the probability of default, valuations, and perceptions of risk. Higher inflows of foreign savings can increase the multiplier further by reducing the domestic savings constraint. The size of the fiscal multipliers is also dependent on the actions of domestic and foreign monetary authorities, thus emphasizing the importance of policy co-ordination.
Keywords: C68; D53; D58; E44; E62; 330; stock-and-flow consistent; financial dynamics; fiscal multipliers; South Africa